Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Budikdamber Dengan Sistem Aquaponik di Desa Capang Purwodadi Pasuruan - Bashori, Hasan (LPPM Universitas Yudharta Pasuruan, 2019)
Capang Village is a village located in Purwodadi District, Pasuruan Regency. Capang village has multiple livelihoods including agriculture, animal husbandry, fisheries, trading, etc. One of the fisheries commodities that has been applied in Capang Village is catfish cultivation, but now it is starting to fade and be abandoned. With this situation, the Community Group 3 Yudharta University of Pasuruan service team introduced or provided BUDIKDAMBER training (aquaculture in a bucket) with the Aquaponics system, later it was hoped that it could regain community interest in conducting fish farming, especially catfish cultivation supplemented with plant cultivation. The main target of this program is PKK Capang village mothers so that they can fill their free time with more useful and beneficial activities. The method used in this program is to use the method of direct socialization, seminars and practice. The practice was carried out by conducting a demonstration of the making of BUDIKDAMBER and Aquaponics, as well as giving BUDIKDAMBER assemblies to several residents as a pilot. The results obtained from this program are an increase in knowledge, especially PKK women in Capang Village, Purwodadi District, Pasuruan Regency about the advantages and benefits of BUDIKDAMBER with the Aquaponic system, and can directly practice, manage the cultivation and business management of BUDIKDAMBER with the Aquaponics system